THE IMPLEMENTATION OF IOC USING CUE CARD TO IMPROVE SPEAKING ABILITY FOR THE SEVENTH GRADERS (RETAIN, 2013)
Kemampuan berbicara menjadi sangat penting di dalam belajar bahasa Inggris. Kemampuan berbicara menjadi penghubung anatara individu dan masyarakat untuk menyampaikan ide, pikiran, dan kepercayaan. Oleh karena itu, seorang guru harus mempunyai teknik yang tepat untuk membantu meningkatkan kemampuan berbicara siswa, terutama untuk tujuan akademik. Di dalam skripsi ini, inside – outside circle using cue card diharapkan menjadi teknik yang sangat baik untuk meningkatkan kemampuan berbicara siswa. Tujuan penelitian ini adalah untuk mendeskripsikan penerapan inside – outside circle using cue card dalam pembelajaran berbicara menggunakan teks deskriptif pada siswa kelas VII. Jenis penelitian ini adalah deskriptif qualitative. Subjek pada penelitian ini adalah siswa kelas VIIF di SMP Negeri 1 Jabon. Data dalam penelitian ini diperoleh dari hasil observasi, tugas siswa, wawancara, dan catatan lapangan. Hasil dari observasi menunjukkan bahwa penerapan teknik inside – outside circle using cue card sesuai dengan prinsip-prinsip mengajar kemampuan berbicara. Hasil dari tugas siswa menunjukkan bahwa siswa bisa mendeskripsikan dengan baik setelah penerapan teknik inside – outside circle using cue card. Berdasarkan uraian tersebut, dapat disimpulkan bahwa teknik inside – outside circle using cue card bisa mendorong siswa untuk aktif dalam pembelajaran berbicara. Teknik inside – outside circle using cue card memberikan suasana belajar yang nyaman dimana siswa bisa melatih kemampuan berbicara sekaligus kemampuan mendengarkan. Kata Kunci : inside - outside circle, cue card , teks deskriptif, kemampuan berbicara Abstract Speaking is considered very important in learning English. Moreover, speaking ability linked the individual to society within to deliver ideas, thinking, and beliefs in spoken way. Thus, teachers should have an appropriate technique to help students develop their ability in speaking, especially for academic purposes. In this thesis, inside - outside circle using cue card is offered as a teaching technique which is regarded very powerful for improving students' speaking ability. This research aims to describe the implementation of inside - outside circle using cue card in speaking of descriptive text for the seventh graders. It also aims to know the students’ speaking ability after the implementation of this technique. This study is descriptive qualitative research. The subject of this research is the seventh graders in SMP Negeri 1 Jabon at class VII-F. The data in this research are the result of observation, students' task, interview and field note.The data are analyzed descriptively to answer the research questions. The result of observation showed that the implementation of this technique was in line with theories about five stages in teaching speaking. The teacher’s activity was in line with principles for teaching speaking skill. The result of students' task showed that the students can describe someone well by inside - outside circle using cue card technique.Based on those result, it can be concluded that inside - outside circle using cue card can encourage the students to speak. IOC technique provided an authentic academic setting where the students have to speak and listen to their friend in English as much as possible. Keywords : inside - outside circle, cue card , descriptive text, speaking ability